2018
DOI: 10.1093/ijnp/pyy028
|View full text |Cite
|
Sign up to set email alerts
|

Matrine Exerts Antidepressant-Like Effects on Mice: Role of the Hippocampal PI3K/Akt/mTOR Signaling

Abstract: BackgroundCurrent antidepressants in clinical use always take weeks or even months to exert full therapeutic effects, and sometimes have serious side effects. Thus, it is very necessary to develop novel antidepressants with better efficacy and fewer adverse effects. The present study focused on investigating the antidepressant potential of matrine and its possible mechanisms of action.MethodsThe forced swim test, tail suspension test, and chronic unpredictable mild stress model of depression were used to revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…TrkB‐induced PI3K activity leads to AKT activation, which, once activated, leads to the phosphorylation of mTOR at serine 2448, thereby promoting downstream molecules (Y. Lu et al, ). It has been reported that the upregulation of PI3K/AKT/mTOR signalling in the prefrontal cortex and hippocampus leads to rapid and consistent antidepressant‐like effects (Z. Wu et al, ). In agreement with previous studies, we observed CSDS‐induced depressive symptoms and consequent PI3K/AKT/mTOR signalling downregulation.…”
Section: Discussionmentioning
confidence: 99%
“…TrkB‐induced PI3K activity leads to AKT activation, which, once activated, leads to the phosphorylation of mTOR at serine 2448, thereby promoting downstream molecules (Y. Lu et al, ). It has been reported that the upregulation of PI3K/AKT/mTOR signalling in the prefrontal cortex and hippocampus leads to rapid and consistent antidepressant‐like effects (Z. Wu et al, ). In agreement with previous studies, we observed CSDS‐induced depressive symptoms and consequent PI3K/AKT/mTOR signalling downregulation.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that MT alleviated anxiety and depression symptoms in a mouse model of burn injury by inhibiting JNK-mediated apoptosis/inflammatory signaling, oxidative stress, and reversing the burn-induced down-regulation of BDNF/VEGF in the hippocampus (Khan et al, 2020). Furthermore, Wu et al (2018) demonstrated that MT possessed antidepressant-like effect on mice by activating the PI3K/Akt/mTOR signaling pathway in the hippocampus.…”
Section: Neuroprotective Effect Of Mtmentioning
confidence: 99%
“…Its hyperactivity can lead to the accumulation of corticotropin-releasing hormone, adrenocorticotropic hormone, and corticosterone (CORT), which can lead to neuroinflammation and damage the functional morphology of the brain [20], which is an important risk factor for depression. The phosphatidylinositol-3-kinase/protein kinase B/mammalian target of rapamycin (PI3K/Akt/mTOR) signaling pathway is an important signaling pathway involved in neuronal survival, synaptic morphology, structure formation, and synaptic information transmission [21]. Activation of this pathway protects the nerve from multiple stress injuries and is involved in the process underlying the antidepressant effects [22,23].…”
mentioning
confidence: 99%